DESAIN RAK PENYIMPANAN UNTUK IKATAN ALUMNI POLITEKNIK NEGERI SAMARINDA - Cahyadi, Dwi; Shalahuddin, Aziz (JURNAL KREATIF: DESAIN PRODUK INDUSTRI DAN ARSITEKTUR, 2017)
Shelves as a storage of goods for everyday purposes, it would be easier to find certain items in it. In an effort to meet the needs and satisfy the consumer, the producer first learn the current market conditions. Importance of goods to be able to make arrangements on the collection of goods so it will be easy to find if at any time needed. Goods arranged neatly on the shelf will provide aesthetic value in the room. Politeknik Negeri Samarinda is one of the universities in Samarinda which consists of several organizations such as Ikatan Alumni Politeknik Negeri Samarinda. From a survey that has been done Ikatan Alumni Politeknik Negeri Samarinda still do not have shelf storage of goods. With the design methodology such as preliminary design, design development, and final design.From this problem, it is necessary to design a storage shelf for Ikatan Alumni Politeknik Negeri Samarinda that serves to place documents and certificates, printers, dispensers, and cutlery. It is expected that with this shelf it will facilitate the activities in the room IKA POLNES.